Analysis of platelet‐derived extracellular vesicles in plateletpheresis concentrates: a multicenter study. Issue 6 (10th April 2017) - Black, Anne; Orsó, Evelyn; Kelsch, Reinhard; Pereira, Melanie; Kamhieh‐Milz, Julian; Salama, Abdulgabar; Fischer, Michael B.; Meyer, Eduardo; Frey, Beat M.; Schmitz, Gerd
Abstract : BACKGROUND: Routine quantification of platelet‐derived extracellular vesicles (PL‐EVs) may be useful in the quality control (QC) of platelet concentrates (PCs). The aim of this multicenter study was to establish and validate a consensus protocol for the standardized PL‐EV quantification using conventional flow cytometers. STUDY DESIGN AMD METHODS: Eighty‐six PCs were investigated in five blood transfusion centers (A‐E) on Days 0 and 5. The centers used different apheresis instruments: Trima Accel (n = 56) and/or Amicus (n = 30). PCs were prepared using standard methods (sd‐PCs; n = 73; A‐D) or with pathogen inactivation (PI [PI‐PCs]; n = 13; E). Platelet (PLT) count was determined using conventional hematology analyzers. PLT degranulation (P‐selectin expression in response to thrombin receptor PAR1 activation) and PL‐EVs were analyzed by flow cytometry. RESULTS: During storage, PLT count remained stable in 58 PCs (A, C, E), whereas a decrease was observed in 12 PCs (B). PLT degranulation declined in all PCs (p < 0.001) and PL‐EVs increased in 74 PCs (A, C‐E; p < 0.001). Certain donor variables (e.g., plasma cholesterol, immature PLT fraction) were associated with lower PL‐EVs. In Trima‐produced PCs, PL‐EVs were significantly lower (D) and PLT degranulation was superior compared to PCs prepared with the Amicus (A, D). PL‐EVs were 10‐fold lower in PI‐PCs, compared to sd‐PCs. However, similar QC trends were demonstrated for both PC groups during storage. CONCLUSION: PL‐EV analysis in a QC program of PCs was successfully performed with results comparable among the different centers. PLT degranulation and vesiculation were primarily affected by preparation techniques.